On the limits of the relation of disgust to judgments of immorality - Kayyal, Mary H.; Pochedly, Joseph; McCarthy, Alyssa; Russell, James A. (Frontiers in Psychology, 2015)
Two correlational studies (ns = 400; 90) examined the association of judgments of immorality and disgust (hypothesized in much current research and theory). Across 40 scenarios in Study 1, immorality was positively correlated with negative emotions, especially anger. With anger partialed, disgust was significantly, but weakly, correlated with immorality, r (38) = .22, p <.05. Study 2 asked whether the immorality-disgust correlation is due to a confound: immoral events often include elements implicitly or explicitly implying pathogens, such as blood or semen. Across 22 scenarios, those implying pathogens were associated with disgust, but those without pathogens, whether moral or immoral, rarely were. We propose that the relation between disgust and immorality is largely coincidental, resulting from (a) using the word disgust to express anger with or even dislike of immoral acts and (b) the presence of incidental elements capable of eliciting disgust.